2016
DOI: 10.1111/jocn.13388
|View full text |Cite
|
Sign up to set email alerts
|

Coping styles used by sexual minority men who experience intimate partner violence

Abstract: Aims and objectives The current study examined the coping styles used by sexual minority men who have experienced intimate partner violence (IPV), including sexual, emotional, and physical victimization, as well as physical injury. Background While sexual minority men experience IPV at least as often as do heterosexuals, there is currently limited knowledge of IPV in this community or resources for sexual minority men who experience IPV. Design Cross-sectional design. Method Sexual minority men (N= 89) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 48 publications
0
12
0
2
Order By: Relevance
“…In the follow-up 2015 U.S. Transgender Survey ( N = 27,715), 10% had experienced family violence (this may include experiences of IPV), 47% had been sexually assaulted in their lifetime, 10% had been sexually assaulted in the past year, and 54% had experienced IPV (James et al, 2016). In comparison to non-TGNC sexual minorities, in a study of lifetime prevalence of IPV among non-TGNC sexual minority men, participants reported as follows: 34.8% sexual abuse, 38.2% physical abuse, 69.7% psychological abuse, and 28.1% suffered an IPV-related injury (Goldberg-Looney, Perrin, Snipes, & Calton, 2016). Among a sample of non-TGNC sexual minority women, the following lifetime prevalence of IPV was reported: 25.3% sexually victimized, 34% physically victimized, 76% psychologically victimized, and 29.3% injured because of IPV (Sutter et al, 2019).…”
Section: Prevalence Of Ipv In the Tgnc Communitymentioning
confidence: 99%
“…In the follow-up 2015 U.S. Transgender Survey ( N = 27,715), 10% had experienced family violence (this may include experiences of IPV), 47% had been sexually assaulted in their lifetime, 10% had been sexually assaulted in the past year, and 54% had experienced IPV (James et al, 2016). In comparison to non-TGNC sexual minorities, in a study of lifetime prevalence of IPV among non-TGNC sexual minority men, participants reported as follows: 34.8% sexual abuse, 38.2% physical abuse, 69.7% psychological abuse, and 28.1% suffered an IPV-related injury (Goldberg-Looney, Perrin, Snipes, & Calton, 2016). Among a sample of non-TGNC sexual minority women, the following lifetime prevalence of IPV was reported: 25.3% sexually victimized, 34% physically victimized, 76% psychologically victimized, and 29.3% injured because of IPV (Sutter et al, 2019).…”
Section: Prevalence Of Ipv In the Tgnc Communitymentioning
confidence: 99%
“…We used six items from Carver’s (1997) Brief COPE instrument to assess weekly maladaptive coping behaviors. The Brief COPE has previously been used in research to understand how sexual minority men react to stress in daily life (e.g., Goldberg-Looney et al, 2016; Rood et al, 2015). The six items tap into several components of maladaptive coping (i.e., self-blame, substance use, venting, denial, self-distraction, and behavioral disengagement).…”
Section: Methodsmentioning
confidence: 99%
“…Research (e.g., Goldberg‐Looney et al, 2016; Langenderfer‐Magruder et al, 2016) indicates that simply identifying as a queer woman is a risk factor for IPV victimization. In a study of 150 sexual minority women (Sutter et al, 2019), 34% reported they had experienced physical IPV in their most recent relationship, 76% reported psychological IPV, 25% reported sexual IPV, and 29% reported experiencing an IPV‐related injury.…”
Section: Sexual Minority Womenmentioning
confidence: 99%
“…There is no reason to expect that these effects would not carry over to the LGBTQ+ population, and research would suggest that these health risks might actually be exacerbated by other minority stressors in this population. Research by Goldberg‐Looney et al (2016) suggests that when men experience injury as a result of same‐sex IPV, they are more likely to use religious coping (e.g., prayer) and less likely to use planning coping (e.g., plans to leave the relationship). Both religious coping and planning coping are considered adaptive forms of coping; however, Rostosky et al (2007) suggested that religious coping is not effective for LGBTQ+ people.…”
Section: Parental Healthmentioning
confidence: 99%